An overview of higher education in Myanmar. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2011)
Myanmar is officially known as the Union of Myanmar. In 1962, shortly after the accession to power of the revolutionary government, there were some positive changes in Myanmar’s higher education sector as the University Education Act was passed.